Rekonstruksi Komponen-Komponen Pendidikan Islam dalam Menghadapi Tantangan Era Digital di Sekolah - Misrawati, Misrawati; Jamilus, Jamilus (YASIN, 2025)
Although the reconstruction of Islamic education components has received attention in several studies, research that specifically addresses the adaptation of Islamic education to the digital era in school contexts remains limited. This study aimed to explore the transformation of educational objectives, teacher competencies, student responses, teaching materials, instructional methods, and evaluation of Islamic education in responding to digital challenges. A qualitative approach with a case study design was employed, involving 15 participants comprising six Islamic Religious Education teachers, two principals or vice-principals in charge of curriculum, and seven students selected through purposive sampling based on their experience with digital-based learning. Data were collected through semi-structured interviews, participatory observations, and documentation of teaching materials and assessment results, and were then analysed thematically to identify patterns, themes, and insights related to the adaptation of Islamic education. The findings showed that the objectives of Islamic education seek to balance technological mastery with the internalisation of moral values; teacher competencies developed through digital literacy and pedagogical creativity; teaching materials and instructional methods became more interactive and project-based; and educational evaluation integrated cognitive, affective, and psychomotor aspects in a holistic manner. Anomalous findings indicated persisting limitations in digital literacy, social media distractions, and unequal access to technology among some students. These findings contribute to the development of digitally based adaptive Islamic education theory and broaden understanding of holistic instructional practices. The study underscores the importance of teacher competence and student readiness, and offers practical implications for schools in designing teacher development programmes, interactive teaching materials, and holistic technology-based evaluations, while also opening avenues for further research on the role of digital infrastructure, parental support, and school policies in enhancing the effectiveness of digital Islamic education.